Design to Robotic Assembly: An Exploration in Stacking - Chiang, Yu-Chou; Bier, Henriette; Mostafavi, Sina (Frontiers in Digital Humanities, 2018)
The Design-to-Robotic-Assembly project presented in this paper showcases an integrative approach for stacking architectural elements with varied sizes in multiple directions. Several processes of parametrization, structural analysis, and robotic assembly are algorithmically integrated into a Design-to-Robotic-Production method. This method is informed by the systematic control of density, dimensionality, and directionality of the elements while taking environmental, functional, and structural requirements into consideration. It is tested by building a one-to-one prototype, which is presented and discussed in the paper with respect to the development and implementation of the computational design workflow coupled with robotic kinematic simulation that is enabling the materialization of a multidirectional and multidimensional assembly system.